2016
DOI: 10.1016/j.anpedi.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Etiología bacteriana de la otitis media aguda en España en la era de la vacuna neumocócica conjugada

Abstract: NTHi and Spn were the main etiological agents for AOM in Spain. Impact of pneumococcal vaccination on AOM requires further evaluation in Spain, after higher vaccination coverage rate is reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The prevalence of bacterial pathogens in children with otitis media has been investigated in different European countries [21][22][23][24], but only one study (which analyzed samples from AOM cases with spontaneous otorrhea) has been performed in Portugal [20]. The implementation of the PCV has been reported to impact OM etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of bacterial pathogens in children with otitis media has been investigated in different European countries [21][22][23][24], but only one study (which analyzed samples from AOM cases with spontaneous otorrhea) has been performed in Portugal [20]. The implementation of the PCV has been reported to impact OM etiology.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of children immunized in Europe is high (80%) [29], as were those from which samples were collected (93.88%). After the implementation of PCV, studies reported a change in pathogen dominance from S. pneumoniae to H. influenzae (in France and Greece) [21,22], as well as the replacement of S. pneumoniae serotypes covered by the vaccine by others (in France and Spain) [21,24,30]. Moreover, the high use and misuse of antibiotics may have impacted the prevalence of some bacterial species and serotypes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal colonization precedes pneumococcal disease, is a major factor for horizontal transmission within the community, especially among young children ( 5 ), and reflects the pneumococcal strains circulating in the community ( 6 ). Pneumococci are among the most frequent causes of bacterial AOM ( 7 9 ), which is the most common bacterial infection in children under 3 years of age ( 10 ). Pneumococcal conjugate vaccines (PCVs) interrupt the transmission of antibiotic-resistant pneumococci and thus decrease the burden of disease caused by antibiotic-resistant isolates in immunized children.…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pneumoniae is one of the most common pathogens causing a variety of respiratory infectious diseases, such as otitis media, pneumonia, bacteremia, and meningitis. S.pn includes at least 97 identified serotypes, and 19F is the prevailing human pathogen from the middle ear of otitis media patients (21). So far, the mechanism of the host immune response against S.pn AOM remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%